2013
DOI: 10.1038/emboj.2013.184
|View full text |Cite
|
Sign up to set email alerts
|

Defective immune responses in mice lacking LUBAC-mediated linear ubiquitination in B cells

Abstract: The linear ubiquitin chain assembly complex (LUBAC) plays a crucial role in activating the canonical NF-jB pathway, which is important for B-cell development and function. Here, we describe a mouse model (B-HOIP Dlinear ) in which the linear polyubiquitination activity of LUBAC is specifically ablated in B cells. Canonical NF-jB and ERK activation, mediated by the tumour necrosis factor (TNF) receptor superfamily receptors CD40 and TACI, was impaired in B cells from B-HOIP Dlinear mice due to defective activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
156
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 111 publications
(166 citation statements)
references
References 51 publications
(89 reference statements)
7
156
0
Order By: Relevance
“…However, considering our results described here, together with the previous observation that Lys63-linked chains are dispensable for TNF-␣-mediated NF-B activation (43), it seems likely that linear chain-mediated trans autophosphorylation of IKK2 plays a major role in NF-B activation, at least in the case of activation mediated by the TNF receptor family. In further support of this notion, we observed previously that CD40-mediated NF-B activation is almost completely abolished in B cells from mice lacking the linear polyubiquitination activity of LUBAC (39). Further dissection of the mechanism underlying IKK activation via LUBAC-mediated linear polyubiquitination will be needed to clarify the involvement of linear chain-mediated dimerization of IKK2 in NF-B activation induced by various stimuli, including IL-1␤.…”
Section: Discussionmentioning
confidence: 56%
“…However, considering our results described here, together with the previous observation that Lys63-linked chains are dispensable for TNF-␣-mediated NF-B activation (43), it seems likely that linear chain-mediated trans autophosphorylation of IKK2 plays a major role in NF-B activation, at least in the case of activation mediated by the TNF receptor family. In further support of this notion, we observed previously that CD40-mediated NF-B activation is almost completely abolished in B cells from mice lacking the linear polyubiquitination activity of LUBAC (39). Further dissection of the mechanism underlying IKK activation via LUBAC-mediated linear polyubiquitination will be needed to clarify the involvement of linear chain-mediated dimerization of IKK2 in NF-B activation induced by various stimuli, including IL-1␤.…”
Section: Discussionmentioning
confidence: 56%
“…In contrast, Dubois et al (39) concluded that LUBAC plays a non-catalytic role in antigen receptor signaling and in DLBCL based on the observation that a catalytically compromised mutant of HOIP was able to rescue HOIP-deficient Jurkat T cells in assays that measured TCR-induced NF-B activation. Consistent with the latter, Sasaki et al (40) reported that the inducible deletion of the RBR domain of HOIP, which is required for catalytic activity, in murine B cells had little effect on BCR signaling to NF-B. However, in an unbiased survey of proteins ubiquitinylated during BCR signaling, Satpathy et al (41) discovered that Bcl10 is conjugated with linear ubiquitin chains in response to BCR engagement.…”
mentioning
confidence: 55%
“…In line with this, B-cell receptor-mediated NF-kB activation occurs in splenocytes that lack HOIP catalytic activity. 22 We also show that the LUBAC is integral to preassembled CBM complex in ABC DLBCL lines and guarantees cell survival by maintaining constitutive NF-kB activity. Hence, strategies aimed at targeting the LUBAC might be relevant in the context of ABC DLBCL.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23] Although TNFa treatment efficiently assembled M1-ubiquitin chains that bound to TNFR and SHARPIN, little signal was detected following TCR stimulation ( Figure 1J; supplemental Figure 11). Moreover, TNFa-but not TCR-mediated NF-kB activation was boosted when the negative regulator of LUBAC catalytic activity OTULIN 20,21,24 was silenced (supplemental Figure 12).…”
Section: Resultsmentioning
confidence: 99%